From Complaint to Recovery: Strategic Execution of LAPOR PAK 129 in Protecting Women and Children from Violence - Widiyantoro, Moch Wahyu Adi; Kartini, Dede Sri; Bintari, Antik; Nuphanudin (Journal of Pedagogy and Education Science, 2025)
This study aims to comprehensively describe and analyze the implementation strategy of the LAPOR PAK 129 service in addressing violence against women and children in East Java Province during the 2021–2024 period. The primary focus is to explore the strategy of the LAPOR PAK 129 program, encompassing the stages of program planning, implementation, and its impact on handling cases of violence. A descriptive qualitative approach is employed to examine and interpret the empirical conditions related to the planning, execution, and outcomes of the program. This approach allows for a deep understanding of the real-life context and practices of the LAPOR PAK 129 service in the field. The data collection process combines primary data from direct observation and interviews and secondary data from relevant official documents and reports. To ensure the credibility of the findings, rigorous triangulation methods are applied by integrating various data sources, research techniques, and time frames. This methodological rigor strengthens the reliability and validity of the research results. The findings indicate that the implementation strategy of LAPOR PAK 129 is supported by a program plan with objectives that are clear, specific, measurable, relevant, and time-bound (SMART). Program implementation follows a well-structured action plan and demonstrates effective coordination among key stakeholders, including government agencies and civil society actors. The LAPOR PAK 129 service has had a positive impact, as evidenced by an increase in reported cases of violence, a high percentage of cases being followed up and resolved, and an overall improvement in public satisfaction with the service. These outcomes highlight the program’s effectiveness in strengthening the protection system for women and children in East Java.